Biodiesel Production from Kapok (Ceiba pentandra) Seed Oil using Naturally Alkaline Catalyst as an Effort of Green Energy and Technology - Handayani, N.A.; Santosa, H.; Sofyan, M.; Tanjung, I.; Chyntia, A.; Putri, P.A.R.S.; Ramadhan, Z.R. (International Journal of Renewable Energy Development, 2013)
Nowadays, energy that used to serve all the needs of community, mainly generated from fossil (conventional energy). Terrace in energy consumption is not balanced with adequate fossil fuel reserves and will be totally depleted in the near future. Indonesian Government through a Presidential Decree No. 5 year 2006 mandates an increased capacity in renewable energy production from 5 percent to 15 percent in 2025. C. pentandra seed oil has feasibility as a sustainable biodiesel feedstock in Indonesia. The aim of this paper was to investigate biodiesel production from ceiba petandra seed oil using naturally potassium hydroxide catalyst. Research designs are based on factorial design with 2 levels and 3 independent variables (temperature, reaction time and molar ratio of methanol to oil). According to data calculation, the most influential single variable is molar ratio of methanol to oil. Characterization of biodiesel products meet all the qualifications standardized by SNI 04-7182-2006.Â